The liability of internet service providers for copyright infringement in Sri Lanka: A comparative analysis - Ruwan Fernando (South Centre, 2022)
The exclusive rights enjoyed by a copyright owner to reproduce his protected work in any material form, including any permanent or temporary storage in electronic form will have a direct impact on the lawful activities of an internet service provider (ISP). Any transmission of temporary copies of material protected by copyright law by their subscribers or third parties using the networks provided by an ISP may amount to unauthorised reproduction of such protected material. The exclusive rights granted to a copyright owner may, thus, place an ISP in a difficult position that may seriously affect the legitimate services and facilities provided by an ISP such as transmitting, routing and storing of information on their networks. It would be impracticable however, to equate the position of a person who engages in traditional copyright infringement with that of an ISP who may merely provide access to the internet and various services to its subscribers facilitated by its networks. The making of temporary copies exception was developed in the copyright law to safeguard the legitimate interests of an ISP, which may under certain conditions, exempt an ISP from liability for copyright infringement on the internet initiated by its subscribers or third parties by using the system provided by an ISP. There are laws in force in many countries to limit the liability of an ISP for the infringement of copyright that takes place on its networks. An ISP in Sri Lanka may not enjoy the same privilege for the infringement of unauthorised material initiated by its users or third parties on their networks. The current law is unlikely to provide adequate protection for the legitimate activities of ISPs in an attempt to minimize the vulnerability against copyright infringement claims.
Keywords: 300; Copyright; Copyright Infringement; E-commerce; European Union (EU); Intellectual Property; Internet; Internet Governance; Internet Service Providers (ISPs); Right of Communication; Sri Lanka; United States (US); WIPO Copyright Treaty; World Intellectual Property Organization (WIPO)